ПІДГОТОВКА ВХІДНОЇ ІНФОРМАЦІЇ ДЛЯ АВТОМАТИЧНОЇ КОРЕКЦІЇ ПОХИБОК ВИМІРЮВАЛЬНИХ КАНАЛІВ СТРУМУ СИСТЕМ КЕРУВАННЯ ЕЛЕКТРОЕНЕРГЕТИЧНИМИ ОБ’ЄКТАМИ - Танкевич, Є.М.; Яковлева, І.В.; Варський, Г.М.; Паньків, В.І. (Інститут електродинаміки НАН України, Київ, 2016)
The algorithm for calculating the corrections to the measurement module and phase of the currents depending on the values of these currents and how to obtain information about the errors of the current transformers is developed. On the basis of this algorithm, the program of preparation of input data for the correction of errors of the current measuring channels is developed. Its application allows minimizing the number of operations performed directly in the measuring tool while ensuring the necessary increasing of the accuracy of the measuring channel. References 4, figures 2.